Analisa Ketidaksesuian Beban Kerja Matakuliah Praktek Berbasis Time Study Dan Maynard Operation Sequence Techniques (Most) (Studi Kasus Pada Jurusan Teknik Mesin Politeknik Negeri Ambon) - Pattiasina, Nanse Henny; Soenoko, Rudy; Astuti, Murti; Irawan, Yudy Surya (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
Implementation of the practice course in the Department of Mechanical Engineering Polytechnic of Ambon during this work takes too long, so beyond the allocation of the appropriate amount of time available in the curriculum credits. Therefore it is necessary to analyze the workload mismatch practice course. Stages of student work time measurements performed using the method of Time Study and Maynard Operation Sequence Techniques (MOST) to obtain the normal time and standard time student practical work. Correlation with time available on the course curriculum for the Job Machine Tools 4 the number of credits is 144 hours, then declared for the methods of time study needs more work time (342.6 hours / 5 students), so the result is inadequate (less than 198, 6 hours). As for the method of MOST, obtained the required sufficient time (114 hours / 5 students).Keywords : measurement of time, the burden of college practice, MOST, standard time, normal time